(untitled) (Iraqi Journal of Medical Sciences, 2018)
Background: Depression is a common consequence of spinal cord injury. Objective: To identify the prevalence and potential risk factors of depression among spinal cord injured inpatients, and assessment of the severity of depression. Methods: A cross-sectional study conducted at Ibn Al Quff Hospital for spinal cord injury rehabilitation. All inpatients with traumatic spinal cord injury were recruited excluding severely injured and those injured due to congenital and medical causes. Socio-demographic variables, spinal cord injury characteristics and comorbidity were compiled. Self-Reporting Questioner (SRQ-20) was used to identify mental symptoms. DSM-IV criteria for depression and Hamilton-17 Scale, for assessment of severity of depression were used. Results: A total of 274 spinal cord injured inpatients were approached; 93% responded; Paraplegics 75.7% and tetraplegics 24.3%. Violence was the major cause of injury. Seventy four percent (74.1%) had depression; 44% of them had severe and very severe depression. Depression was significantly associated with age (P=0.001), gender (P=0.001), education level (P=0.038), occupation (P=0.003); smoking habit (P=0.035), duration of injury (P=0.003), times of admission (P=0.000), and comorbidity (P=0.018). Conclusion: prevalence of depression is high and frequent among spinal cord injured inpatients. Demographic and spinal cord injury variables are significantly associated with depression and are the most important determinants of depression. Keywords: Depression, spinal cord, violence, prevalence, Iraq. Citation: Al Abbudi SJR, Ezzat KI, Farhan MS, Zebala AA, Al-Beedany MSJ, Hamdy DJ. Prevalence and determinants of depression among traumatic spinal cord injured patients attending Ibn-Al-Quff Hospital, Baghdad, Iraq. Iraqi JMS. 2017; Vol. 15(4). 383-395. doi: 10.22578/IJMS.15.4.9.